TRANSITIONAL CURRICULUM IN AESTHETIC TEACHING: A TEST FOR SELF-EFFICACY - Reynaldo B. Inocian (European Scientific Journal, ESJ, 2013)
This study is a validation of Albert Bandura’s self-efficacy theory in teaching – a writer’s voice of teaching experience in more than two decades, in basic and tertiary education from 1991 to 2012. The use of grounded theory and content analysis revealed that his self-efficacy judgments served as basis for behavior performance in promoting excellence in the job within the past twenty years of his career more specifically in curriculum realignment. Four considerations of Tyler’s Cyclical Model determined the underlying factors and processes for curriculum revision. Content units and chapters of the three revised books were realigned according to the recommended competency standards of DepEd, CHED, and PRC. Teaching pedagogies in these books were analyzed according to Johnson’s philosophical models. Success stories of graduates about the use of these books on Aesthetic Teaching Pedagogies were also documented. All these variables were juxtaposed to establish the writer’s self-efficacy. Self-efficacy is an edge for successful curriculum innovation and excellence in instruction that determine a successful learning outcome.